2012
DOI: 10.1007/s00436-012-2879-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of rBm86 against Rhipicephalus (Boophilus) microplus (IVRI-I line) and Hyalomma anatolicum anatolicum (IVRI-II line) infestations on bovine calves

Abstract: With an aim to evaluate the protective potentiality of rBm86 against Rhipicephalus (Boophilus) microplus Indian Veterinary Research Institute (IVRI)-I line and Hyalomma anatolicum anatolicum IVRI-II line infestations on crossbred (Bos indicus × Bos taurus) calves, 20 animals of 3 months of age were randomly divided in to four equal groups and maintained in tick-proof conditions. Animals of groups 1 and 2 were immunized with 2 ml of rBm86 (100 μg)-based vaccine (procured from Revetmex S.A. de C.V, Mexico City, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
3
14
0
Order By: Relevance
“…The divergence level of more than 2.8% has been reported as a limiting factor in the variation of efficacy of the Bm86-based vaccines [27,29]. The sequence divergence data validates the earlier observation in which 44.5% and 25.1% efficacy against R. microplus (IVRI-I strain) and Hyalomma anatolicum (IVRI-II strain), respectively, was recorded in a pen trial using commercial Cuban Bm86 vaccine [44]. The high diversity of IVRI-I Bm86 and low efficacy of commercial Mexican Bm86 vaccine in India showed that there is a strong need foran Indian-specific Bm86 vaccine.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The divergence level of more than 2.8% has been reported as a limiting factor in the variation of efficacy of the Bm86-based vaccines [27,29]. The sequence divergence data validates the earlier observation in which 44.5% and 25.1% efficacy against R. microplus (IVRI-I strain) and Hyalomma anatolicum (IVRI-II strain), respectively, was recorded in a pen trial using commercial Cuban Bm86 vaccine [44]. The high diversity of IVRI-I Bm86 and low efficacy of commercial Mexican Bm86 vaccine in India showed that there is a strong need foran Indian-specific Bm86 vaccine.…”
Section: Discussionsupporting
confidence: 85%
“…A variation greater than 2.8% in the amino acid sequence of the protein expressed would be sufficient to confer variable efficacy [27]. Partial protection in earlier pen trials [44] with the Cuban rBm86 vaccine, Gavac in India indicated variation in the Indian Bm86 gene sequence. However, investigations have not been conducted to identify the level of diversity in the Bm86 gene within the Indian strains of R. microplus and how this compares to the globally available strains.…”
Section: Introductionmentioning
confidence: 99%
“…This strongly suggests that a universal tick vaccine is nonviable and that focus should be placed on finding targets within subsets of closely related tick genera or even species. Cautions should thus be placed on extrapolating the protective abilities of a specific antigen between tick species, as was seen in the case of Bm86 vaccines and a vast number of antigens that failed to protect against different tick species across different hosts (as summarized in Ref. ).…”
Section: Insight From Tick Protein Evolution: Targeting Of Binding Spmentioning
confidence: 99%
“…In an attempt to develop cross-protective vaccine, Rodriguez-Valle et al (2012) immunized cattle and camels with rBm86-based vaccine and challenged with H. dromedarii and A. cajennense ticks and recorded partial efficacy against former tick and no effect against later tick species. Similarly, cross-protective efficacy of Gavac™ was assessed against H. anatolicum, Indian isolate and 25 % efficacy was recorded (Kumar et al, 2012b). The cross-protective efficacy of rHaa86, SUB, CRT and CathL was also tested against R. microplus but the results were not much encouraging and revealed that the species-specific vaccine is more efficacious (Kumar et al, 2017).…”
Section: Immunization Of Hostsmentioning
confidence: 99%